KETAHANAN EKONOMI PADA MASA PANDEMI DI KAMPUNG CIKALAPA, DESA RAJAMANDALA KULON, KECAMATAN CIPATAT, KABUPATEN BANDUNG BARAT - `Agustina Rahayu, Resti; Elmania Rahayu, Elmania; Nursafitri, Gita; Dwi Utari, Destriana; Cahyati, Lisna; Sapitri, Neng; Rahmawati, Nuraida; Elsa Novita Wardani, Elsa; Aulia, Retania; Imaroh Nusaibah, Siti Ummu; Solihin, Dadin (Jurnal Istimā, 2024)
This research was initially motivated by a community service program aimed at understanding the economic resilience of village communities during the pandemic. The study examines the development of the village, the understanding of Islamic economics in economic activities, the community's awareness, and the role of the social institution "Karang Taruna" in the village. The purpose of this research is to gain a deeper understanding of the village's economic resilience. The research methodology employed is qualitative-descriptive, involving observations, interviews, and a comprehensive review of theoretical references. The findings reveal that many economic activities in the village have already adopted macroeconomic principles, with small and medium enterprises (SMEs) such as garment production and brick manufacturing. However, in terms of economic support, such as capital loans, the community still relies on conventional financial institutions. The conclusion drawn from the findings is that the village residents have not yet been able to contribute optimally to the community during the COVID-19 pandemic. Penelitian ini bermula dari motivasi program kuliah kerja nyata untuk memahami ketahanan perekonomian masyarakat desa selama pandemi. Riset ini mengkaji perkembangan desa, pemahaman ekonomi syariah dalam aktivitas ekonomi, tingkat pemahaman masyarakat, serta peran lembaga sosial “Karang taruna” di desa tersebut. Tujuan penelitian ini adalah untuk menggali lebih dalam tentang ketahanan perekonomian desa. Metode penelitian yang digunakan adalah kualitatif-deskriptif melalui observasi, wawancara, dan kajian literatur komprehensif. Hasil penelitian menunjukkan bahwa banyak kegiatan ekonomi di desa telah menggunakan prinsip-prinsip ekonomi makro, seperti usaha kecil menengah (UMKM) di bidang konveksi dan produksi batu bata. Namun, untuk mendukung perekonomian, seperti dalam hal pinjaman modal, masyarakat masih bergantung pada lembaga keuangan konvensional. Kesimpulannya, kontribusi ekonomi masyarakat desa belum optimal dalam menghadapi situasi pandemi COVID-19.